Literary intelligence analysis of novel protagonists' personality traits and development. (27th July 2018) - Liu, Mingming; Wu, Yufeng; Jiao, Dongdong; Wu, Michael Shengtao; Zhu, Tingshao
Abstract: Digital technology is drawing more and more research attention in many areas of humanities because of its advantages in objectivity and automation. This work was an attempt to analyze two protagonists' personality traits and development, through their dialogues in a Chinese novel Ordinary World . We used language technology LTP, a Simplified Chinese segmentation software, to segment dialogues. Then, on the basis of eighty-eight LIWC (Linguistic Inquiry and Word Count) features, personality predictive models were recruited to calculate the Big Five personality. We obtained two sets of predicted Big Five personality scores through dialogues in general and those before versus after the protagonist's life events (high-school graduation and marriage). As expected, the two protagonists' (Shaoping Sun and Shaoan Sun) Big Five personality traits were coincided with the portraits in the novel, and the two protagonists showed observable personality development after their life events, which was consistent with previous studies on personality change. This work demonstrates the applicability and validity of literary intelligence analysis in humanistic texts, suggesting a reliable approach to analyze novel protagonists' personality in an objective manner.